Relevansi Tasawuf Cinta Ilahi Rabi’ah al-Adawiyah terhadap Problem Radikalisme Beragama di Indonesia - Mohamad Za'in Fiqron; Erina Dwi Parawati (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2023)
Abstract This article aims to understand and explain the significance of Rabi'ah al-Adawiyah's love of Sufism in the Contemporary religious context. Rab'iah Adawiyyah is a female Sufi who was admired by many Sufis after her and quoted by the Sufis of love in particular. Rab'ah al-Adawiyah made a huge contribution to the discipline of Sufism, namely al-Mahabbah. The method of this article is based on qualitative documentation as a data collection technique. Data were obtained from various literature relevant to this research topic, then analyzed using Hans-Georg Gadamer's hermeneutic theory. Gadamer's contribution in text interpretation is the concept of fusion horizons, in which there is a fusion of understanding between the horizons of the reader and the writer. The resulting meaning is not reproductive, but productive. So that the concept of Sufism Rabi'ah can be read in the contemporary horizon. The results of this study show that Rab'iah's ideas about love can be the answer in reviving the inner subjectivity or dimension of religious spirituality in the midst of religious problems. As is known, if religion is not lived with love, it will give birth to fundamentalism, radicalization, and religious conflict. This reading is very important, in the midst of the glitz of technology and the hustle and bustle of modernity, studying Sufism will more or less help in treating the crisis of spirituality. Keywords: Contemporary Religion, Women Sufi’s, Rabi'ah al-Adawiyah. Abstrak Artikel ini bertujuan memahami dan menjelaskan signifikansi tasawuf cinta Rabi’ah al-Adawiyah dalam konteks keberagamaan Kontemporer. Rab’iah Adawiyyah adalah sufi perempuan yang dikagumi oleh banyak sufi setelahnya dan dikutip oleh kalangan sufi cinta pada khususnya. Rab’ah al-Adawiyah memberikan sumbangsih amat besar bagi disiplin tasawuf, yakni al-Mahabbah. Metode artikel ini berbasis kualitatif dengan dokumentasi sebagai teknik pengumpulan data. Data diperoleh dari berbagai literatur yang relevan dengan topik penelitian ini, kemudian dianalisis memakai teori hermeneutika Hans-Georg Gadamer. Sumbangsih gadamer dalam penafsiran teks ialah konsep fusi horizon, di mana terjadi peleburan pemahaman antara horizon pembaca dengan penulis. Makna yang dihasilkan bukanlah reproduktif, melainkan produktif. Sehingga konsep tasawuf Rabi’ah dapat dibaca dalam horizon kekinian. Hasil penelitian ini memperlihatkan bahwa gagasan Rab’iah tentang cinta mampu menjadi jawaban dalam menghidupkan innersubjektivitas atau dimensi spiritualitas agama di tengah problematika keagamaan. Sebagaimana diketahui, manakala agama tidak dihayati dengan cinta, akan melahirkan fundamentalisme, radikalisasi, dan konflik keagamaan. Pembacaan ini amat penting, di tengah gemerlapnya teknologi dan hiruk-piruk modernitas, mengkaji tasawuf sedikit-banyak akan membantu dalam mengobati krisis spiritualitas. Kata Kunci: Keberagamaan Kontemporer, Sufi Perempuan, Rabi’ah al-Adawiyah.